Ecology, distribution and control of the invasive weed Nassella trichotoma (Nees) Hack. ex Arechav.: A global review of current and future challenges. (26th October 2020) - Humphries, Talia; Dowling, Kim; Turville, Christopher; Sinclair, Steve; Florentine, Singarayer
Abstract: Nassella trichotoma (serrated tussock) is a highly invasive perennial C3 weed from South America. It grows in most soil conditions, can resist fire and frost, and is unpalatable to grazing animals. Each plant can produce up to 140, 000 seeds annually, and together, these characteristics make it a damaging landscape weed. It has diminished the agricultural carrying capacity of pastures in south‐eastern Australia, New Zealand and South Africa, and emerging populations have now been identified in Europe and the United States, and bioclimatic models suggest its distribution could significantly expand within these regions in the near future. Research into control methods for this weed has been explored, and these include herbicides applied alone and in combination, the establishment of plant competition, the introduction of seed mitigation fencing, grazing management and exclusion zones, specific biological management and alteration of soil composition. Currently, the most effective and widely used control method is the residual herbicide flupropanate (2, 2, 3, 3‐tetrafluoropropanoic acid). This review will investigate the ecology, distribution, current control techniques and past research on this species, and make recommendations for future research and management.